THE IMPORTANCE OF DIALOGICAL COMMUNICATIVE STRUCTURES IN THE PROCESS OF TEACHING DIALOGICAL COMMUNICATION SKILLS IN THE MOTHER LANGUAGE (American Journal of Interdisciplinary Research and Development, 2025)
This scientific paper explores the essence of dialogic communicative structures, their role in developing students’ oral speech, and their methodological significance in teaching dialogic communication skills in native language classes. The study analyzes the potential of such structures to enhance active listening, opinion expression, dialogue participation, and adherence to speech etiquette among students. Particular attention is given to communication-based teaching methods, such as question–answer exercises, role-plays, and dialogic tasks, which foster the development of communicative competence. The findings emphasize the importance of integrating a communicative approach into native language instruction as a key direction in modern pedagogy.